Chemical constituents from Bidens bipinnata Linn. (August 2018) - Hu, Hai-Min; Bai, Shu-Min; Chen, Li-Jiao; Hu, Wen-Yi; Chen, Guang
Abstract: The phytochemical investigation on Bidens bipinnata Linn. (Asteraceae) led to the isolation and identification of 38 compounds, including nine ceramides (1 –9 ), thirteen flavonoids (10 –22 ), five phenylpropanoids (23 –27 ), four aliphatics (28, 35–37 ), one pyrimidine (29 ), four steroids (30 –33 ), one triterpenoid (34 ) and one polyacetylene (38 ). All chemical structures were established on the basis of MS and NMR spectroscopic data. In addition to five newly reported compounds (2S, 3S, 4R, 8E)-2-(2′(R), 3′(R)-dihydroxytriocosanoylamino]-8-octadecene-1, 3, 4-triol (1 ), (2S, 3S, 4R, 8E)-2-[(2′R)-2′-hydroxytetracosanoylamino]-10-octadecene-1, 3, 4-triol/(2S, 3S, 4R, 8E)-2-[(2′R)-2′-hydroxytriocosanoylamino]-10-octadecene-1, 3, 4-triol (2 /3 ) and (2R) isookanin-4′-methoxy-7- O -β-d -glucopyranoside/(2S) isookanin-4′-methoxy-7- O -β-d -glucopyranoside (10 /11 ), nine compounds (4 –9, 25, 26, 38 ) were isolated from the Bidens genus for the first time. Meanwhile, the compounds12, 13, 16–21, 30 –34 were reported firstly from Bidens bipinnata Linn. On the basis of chemical research, the chemotaxonomic significance of the isolated compounds has been summarized. Graphical abstract: Highlights: Thirty-eight compounds were isolated from Bidens bipinnata Linn. Nine ceramides with 3 new structures were reported in Bidens genus for the first time. Two newly identified flavanones were firstly isolated from Bidens genus and Asteraceae family. Two simple phenylpropanoids were also obtained from Bidens genus for the first time.